DALAM KIDUNG BHRAMARA SAá¹„U PATI - Putra, I Gde Agus Dharma; Sutjaja, I Gusti Made; Putra, Ida Bagus Rai; Sudarsana, I Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Kalangwan is state of Beauty and cause melting of the distance between the seeker and the sought after. The melting distance causes the soul to drift into the sublime beauty. Distance not only as the conception of space and time, but also the consciousness that separate subject and object. Melting distance means the dissapearance of space, time, and consciousness. Such a condition become a goal by Kawi.Bhramara Sangu Pati more like a monologue that contains the expressions of love for the godness. Love expressions of hope, disappointment, sadness, beauty, especially the longing. Such expressions are axpressed in a soft metamorphosis. Literary is a kind of literature that is still in vague areas especially for researchers.Kalangwan in this text does not stop only on the aesthetic, but also the miystical. Aesthetic because it is a literary work of a hymn that has its own prosody. Mystical because in it there are teachings, especially the teachings that can be used as death. Kalangwan in this study is the level that mustÂ be followed by those who want to achieve death. Kalangwan is not abolished, but skipped. Its like climbing a ladder, to get to the tenth step, it must be through the first, second, third and so on.